MEDIA CETAK MENJADI TRENDSETTER BAHASA? KOHESI DAN KOHERENSI - Rosita Sofyaningrum; Nur Habibah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
Writing in newspaper should be a trendsetter in the use of language. The aim of the study is to describe: 1) the type of cohesion used in Suara Merdeka about education discourse in January-March 2020 edition; 2) the type of coherence used in Suara Merdeka about education discourse in January-March 2020 edition. The data used are texts containing cohesion and coherence markers in the data source in the form of Suara Merdeka about education discourse in January-March 2020 edition. Data were collected by library techniques and analyzed by impulse techniques, substitution techniques, and insertion techniques. The results of the study concluded that: 1) the use of cohesion in the Suara Merdeka about education discourse in January-March 2020 edition can be divided into two namely lexical and grammatical cohesion. The type of lexical cohesion found is only hyponym and the type of grammatical cohesion found in this paper are reference, substitution, impregnation, and conjunction; 2) the use of coherence in Suara Merdeka about education discourse in January-March 2020 edition can be divided into two namely signable coherence and non-signable coherence. The types of signified coherence found in this paper are contrast coherence and sequential coherence. moreover, There were two types of unmarked coherence, namely detail coherence and perian coherence. Keywords: cohesion, coherence, and discourse